Broad coverage of neutralization-resistant SIV strains by second-generation SIV-specific antibodies targeting the region involved in binding CD4. - Hugh C Welles; Hannah A D King; Leonard Nettey; Nicole Cavett; Jason Gorman; Tongqing Zhou; Yaroslav Tsybovsky; Renguang Du; Kaimei Song; Richard Nguyen; David Ambrozak; Amy Ransier; et al. (PLoS Pathogens)
Both SIV and SHIV are powerful tools for evaluating antibody-mediated prevention and treatment of HIV-1. However, owing to a lack of rhesus-derived SIV broadly neutralizing antibodies (bnAbs), testing of bnAbs for HIV-1 prevention or treatment has thus far been performed exclusively in the SHIV NHP model using bnAbs from HIV-1-infected individuals. Here we describe the isolation and characterization of multiple rhesus-derived SIV bnAbs capable of neutralizing most isolates of SIV. Eight antibodies belonging to two clonal families, ITS102 and ITS103, which target unique epitopes in the CD4 binding site (CD4bs) region, were found to be broadly neutralizing and together neutralized all SIV strains tested. A rare feature of these bnAbs and two additional antibody families, ITS92 and ITS101, which mediate strain-specific neutralizing activity against SIV from sooty mangabeys (SIVsm), was their ability to achieve near complete (i.e. 100%) neutralization of moderately and highly neutralization-resistant SIV. Overall, these newly identified SIV bnAbs highlight the potential for evaluating HIV-1 prophylactic and therapeutic interventions using fully simian, rhesus-derived bnAbs in the SIV NHP model, thereby circumventing issues related to rapid antibody clearance of human-derived antibodies, Fc mismatch and limited genetic diversity of SHIV compared to SIV.